Taming the Monster Journal: A Hug to the Numerous Reviewers - Beyer, Christian; Bockwoldt, Juliane C.; Hammar, Emil Lundedal; Pötzsch, Holger (Nordlit, 2019)
To you, dear reviewers: Your monstrous support was, as so often, unpaid—but valuable indeed. The energy you have put together in writing your thorough reviews substantially helped in shaping and re-shaping (and sometimes even re-re-shaping) the wonderful scientific endeavors of our authors. Thank you so much!